Mineral policy of Tanzania and corporate social responsibility around mining communities in Msalala district - Kilave, Jonas Raphael (Mzumbe University, 2023)
A dissertation submitted in partial fulfillment of the requirements of the Degree of Masters of Science in Development Policy (Msc. DP) of Mzumbe University